Refórmese la ley orgánica de régimen tributario interno, con respecto a imponer un impuesto a la contaminación ambiental, por parte de las empresas o industrias que provoquen emisiones contaminantes - Maldonado Ruiz, Mercy Yesenia (2017)
The Constitution of the Republic of Ecuador, Article 14 states: "The right of people to live in a healthy and ecologically balanced environment that ensures sustainability and good living, sumak kawsay. It is of public interest environmental preservation, conservation of ecosystems, biodiversity and integrity of the genetic heritage of the country, prevention of environmental damage and the recovery of degraded natural areas ". Organic Law on Internal Taxation, Chapter I, Tax Environmental Vehicular Pollution in its unnumbered article ... notes: "Object Imponible.- Créase Environmental Pollution Tax Vehicle (AEFI) levied on environmental pollution caused by the use of motorized road vehicles. " This problem has its origin in the situation of lack of a tax on the Organic Law of Internal Tax Regime, so that society contributes to develop and maintain a clean and unpolluted environment, because in most of legislation in the world, society pays taxes in favor of the environment. So we have to create a culture based on respect for the land and the conservation of our natural resources, it is important that we know about the damage we do to our planet. In our country is clearly, environmental pollution produced by companies or industries, which increasingly deteriorates closer to nature, and that governments do not contemplate environmental policies true, to preserve the environment and good living as determined by the Constitution of the Republic of Ecuador. While not concienticemos us from such enormous damage we are doing to pollute the earth, you can not do anything to try to save what we still have of nature. For the above, I propose the Organic Law of Internal Tax Regime is reformed, where a Chapter of Environmental Pollution of Companies or Industries Taxes, causing emissions, to make possible to better protect the rights of nature is included and the rights of all people to live in an ecologically balanced environment that ensures sustainability and good living, as established by the Constitution.